City Library System - Sugra Begum, R. (Journal of Information and Knowledge, 1964)
On the basis of the Census of 1961, calculates the number of City Central Libraries and City Branch Libraries to be established in each Constituent State and in each city respectively. Shows the total number required for India as a whole to be 112 City Central Libraries and 1,510 City Branch Libraries. States that the maintenance of such a City Library System is necessary to prevent the literates, who form 50 per cent of the city population, from relapsing into illiteracy.